Persistent circulation of vaccine serotypes and serotype replacement after 5 years of infant immunization with 13-valent pneumococcal conjugate vaccine in the United Kingdom - Kandasamy, R; Voysey, M; Collins, S; Berbers, G; Robinson, H; Noel, I; Hughes, H; Ndimah, S; Gould, K; Fry, N; Sheppard, C; Ladhani, S; et al. (Oxford University Press, 2019)
Background: Following programmatic introduction of the 13-valent pneumococcal conjugate vaccine (PCV13), there is residual carriage and disease due to PCV13-covered serotypes. Methods: PCV13-immunized children aged 13–48 months, N = 988, were enrolled between February 2014 and August 2015 (“late PCV13”), and had nasopharyngeal pneumococcal carriage compared with 7-valent pneumococcal conjugate vaccine (PCV7) immunized children, N = 567, enrolled between November 2010 and September 2011 (“early PCV13”). Nasopharyngeal pneumococci were molecular-serotyped by microarray. Invasive pneumococcal disease (IPD) cases were identified through enhanced national surveillance. Results: Compared with PCV7-immunized children, carriage among PCV13-immunized children was significantly lower for serotypes 19A (odds ratio [OR], 0.08 [95% confidence interval CI, .02–.25]), 6C (OR, 0.11 [95% CI, .03–.32]), and 7F (8 vs 0 cases). IPD incidence in children <5 years was significantly lower for serotypes 1 (incidence rate ratio [IRR], 0.03 [95% CI, 0–.19]) and 7F (IRR, 0.13 [95% CI, .05–.36]) but not 19A (IRR, 0.6 [95% CI, .3–1.12]) or serotype 3 (IRR, 2.3 [95% CI, .86–6.15]) in the late PCV13 period than in the early PCV13 period. The most significant rises in IPD incidence were for serotypes 8, 12F, and 24F. Conclusions: PCV13 has reduced serotype 19A carriage among vaccinated children. We found no impact of PCV13 on serotype 3 carriage or disease, and emergence of non-PCV13-serotype disease.